PERBANDINGAN LUAS LESI PADA FOTO RONSEN TORAKS ANTARA PASIEN TUBERKULOSIS PARU KASUS BARU BTA POSITIF DENGAN BTA NEGATIF STUDI KOHORT RETROSPEKTIF DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Destriana, Desy; Rahmawati, Indah; Mulyanto, Joko (MANDALA of Health, 2014)
Pulmonary tuberculosis (Pulmonary TB) infected one third of the world population. Since 2009, Indonesia was  the fifth that had the highest tuberculosis case in the world. In 2011, Case Detection Rate (CDR) of Central Java was 49,24%. The prevalence of pulmonary TB in RSUD Prof. dr. Margono Soekarjo  Purwokerto was 472 patients in 2012 until August 2013. Chest x-ray was the first investigation to diagnose pulmonary TB. The aims of this study was to knowing the differences  of lesion area on chest x-ray between new cases of  pulmonary TB patient with AFB smear  positive and AFB smear negative. This is  an Observational analytic with cohort retrospektif study, conducted 22 pulmonary TB patients with AFB smear positive and 22 pulmonary TB patients with AFB smear negative in RSUD Prof. dr. Margono Soekarjo Purwokerto. Data were analyzed by Chi-square with significance level of p<0,05. Univariate analysis showed that the highest number of respondents were male (56,8%), and the highest of the age group  was 15-25 years old group (27,3%). Bivariate analysis using Chi-square was obtained  p= 0,011 (p<0,05). There were differences lesion area on chest x-ray between new cases of  pulmonary TB patient with AFB smear positive  and AFB smear negative.